Tourism and Economic Development in Eastern Europe and the Soviet Union - Hall Derek R (Belhaven Press, 1991)
Preface, Change and Continuity, Introduction, Tourism Opportunities in Eastern Europe and the Soviet Union, Eastern Europe and the Soviet Union: Overcoming Tourism Constraints, Evolutionary Pattern of Tourism Development in Eastern Europe and the Soviet Union, National Studies, The Soviet Union, Eastern Germany (the Former German Democratic Republic), Czechoslovakia, Hungary, Poland, Romania, Bulgaria, Yugoslavia, Albania, Into the 21st Century, Contemporary Challenges, Appendix: Supplementary Literature Sources, Bibliography, Index.